The Analisis Faktor Risiko Leukosituria Pada Pasien Diabetes Di Desa Uteun Kot Kota Lhokseumawe - Sofia, Rizka; Yuziani; Fitria , Dinda; Atika , Khania (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
Diabetes mellitus (DM) is a chronic disease that is still a problem in Indonesia. DM occurs when there is an increase in the level of glucose in the blood (hyperglycemia), in which the body cannot produce enough insulin or use insulin effectively. It is important for DM patients to comply with a series of examinations such as controlling blood sugar so that subjective complaints do not occur that lead to complications. DM patients are at risk for chronic macrovascular complications in the form of infections, ranging from simple to complex infections. This study aims to determine and analyze risk factors for leukocyturia in DM patients in Uteun Kot Village. The research designs used were a laboratory examination and a survey using a questionnaire with a cross-section approach. Laboratory examinations were carried out on the urine of patients with diabetes mellitus (DM) to determine the incidence of leukocyturia and blood sugar levels to determine the blood sugar values of DM patients. The number of samples used in this study was 85 samples that met the criteria determined by using the Slovin formula. sampling using the sequential random sampling method. The variables used in this study were leukocyturia as the dependent variable and gender, duration of illness, and blood sugar levels as independent variables. Leukocyturia laboratory examination by urinalysis and microscopic examinationThe data analysis method used univariate analysis and bivariate analysis. The results showed that 68.2% of DM patients in Uteun Kot Village had leukocyturia, 63.5% of DM patients had high KGDS, and 71.8% had suffered from DM for more than 5 years. The variable duration of suffering from DM has a significant relationship with leukocyturia, where respondents with long suffering from DM above 10 years have a positive probability of leukocyturia 3.72 times compared to those suffering from DM under 10 years. Similarly, DM patients with uncontrolled blood sugar levels have a positive probability of leukocyturia 2.51 times compared to DM patients with controlled blood sugar levels.